(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to discover the personality traits of the pet owners in Brgy. Pasong Putik, Quezon City, by utilizing the Big Five Personality Traits. This study will mainly identify and assess the impact of personality on pet ownership, as well as the factors that affect the pet owner’s personality in terms of companionship, social support, and animal welfare. This study is limited to fifty (50) male and female pet owners between the ages of 18 - 25 (young adults). Agreeableness got the highest weighted mean (x = 3.60) with the verbal interpretation “moderately accurate.” Consciousness got the second to the highest weighted mean (x = 3.24), Openness to Experience got a 3.23 weighted mean, Extraversion got a 2.93 weighted mean, and lastly, Neuroticism got the lowest weighted mean (x = 2.88) with the same verbal interpretation of “neither inaccurate nor accurate.” The overall weighted average mean score of 3.49 showed that the respondents “strongly agreed” with pet companionship, social support, and animal welfare. According to the findings of this study, the majority of respondents are males who scored highly in the personality trait "Agreeableness," while "Neuroticism" received the lowest scores residing in Brgy. Pasong Putik, Quezon City. The respondents also "strongly agreed" with pet companionship, social support, and animal welfare as determining the factors of personality traits of the pet owners.